Electricity and Magnetism - Dr. Yousf Islem BOUREZG (University of M'sila, 2025)
This handout on electricity and magnetism is intended for students in the Science and Technology field at the first License of, Engineering, and LMD levels. It can also be used by students in the Materials Science field. The objectives of this course are to acquire basic concepts on electric charges, the electric field, electric potential, conductors, and electrical circuits. The course manuscript is structured around five chapters: - Electric Charge and Coulomb's Law, - Electric Field and Potential, - Electric Dipole and Gauss's Law, - Conductors and Capacitors, - Electrical Current and Resistors, At the end of each chapter, a series of corrected and uncorrected exercises are provided for students. Finally, we conclude this course with a general bibliography. We hope that this course will serve as a reference for students and help them in their graduate studies. Dr.
Courses and Exercises Corrected